2021
DOI: 10.1021/acs.jpca.0c09882
|View full text |Cite
|
Sign up to set email alerts
|

Unimolecular Reactions Following Indoor and Outdoor Limonene Ozonolysis

Abstract: Limonene is one of the monoterpenes with the largest biogenic emissions and is also widely used as an additive in cleaning products, leading to significant indoor emissions. Studies have found that the formation of secondary organic aerosols (SOAs) from limonene oxidation has important implications for indoor air quality. Although ozonolysis is considered the major limonene oxidation pathway under most indoor conditions, little is known about the mechanisms for SOA formation from limonene ozonolysis. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 103 publications
5
40
1
Order By: Relevance
“…However, one 6-membered ring closure with a nitrate group shows a larger difference of a factor of 50 relative to the non-oxygenated RO 2 studied in this work. Data on b-carbonyl-substituted RO 2 radicals by us and by Chen et al 27 (see Table 2) likewise suggests an impact of over an order of magnitude. Finally, some unsaturated RO 2 radicals with a second unsaturation in b-position to the peroxy radical, CH 2 QCH-C(QCH 2 )CH 2 OO , are reported to be less reactive 26 towards ring closure than suggested by the SAR.…”
Section: Spectator Substituentsmentioning
confidence: 53%
See 1 more Smart Citation
“…However, one 6-membered ring closure with a nitrate group shows a larger difference of a factor of 50 relative to the non-oxygenated RO 2 studied in this work. Data on b-carbonyl-substituted RO 2 radicals by us and by Chen et al 27 (see Table 2) likewise suggests an impact of over an order of magnitude. Finally, some unsaturated RO 2 radicals with a second unsaturation in b-position to the peroxy radical, CH 2 QCH-C(QCH 2 )CH 2 OO , are reported to be less reactive 26 towards ring closure than suggested by the SAR.…”
Section: Spectator Substituentsmentioning
confidence: 53%
“…One of the pathways that enables the oxidation of double-bonded carbons in a molecule is a ring closure reaction: (R2) Ring closure reactions in RO 2 and alkoxy radicals have been studied theoretically, [20][21][22][23][24][25][26][27] and mechanisms incorporating these reactions for some compounds 28 have been shown to provide a better agreement with experimental data. Still, these studies focused on a subset of molecules, and no structure-activity relationship (SAR) is available to enable systematic inclusion of such ring closure reactions in atmospheric chemical mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Neither is particularly fast and slower than the competing bimolecular reactions . Under pristine atmospheric conditions, the bimolecular reactions have a pseudo-first-order rate coefficient of about 10 –2 s –1 (Section S7). Under the experimental conditions of the photoreactor, the bimolecular reaction rate coefficients are expected to be even higher, due to the higher NO concentration (not measured).…”
Section: Resultsmentioning
confidence: 99%
“…The model tends to overestimate the measured ratio by a factor of 2 to 3 during the mopping episodes, as well as during most of the background periods, suggesting that the model may be underestimating the rate of conversion of RO 2 to HO 2 in the ozonolysis mechanism both during the mopping and when constrained by the background concentrations. A recent theoretical study suggests that the peroxy radicals formed from the ozonolysis of limonene can undergo unimolecular reactions at rates fast enough to compete with reactions with NO under typical indoor conditions ( 52 ). This is further supported by the experimental study of Pagonis et al ( 27 ) in a university art museum, where measurements of indoor HOM production from limonene ozonolysis suggested that unimolecular isomerization was an important fate of RO 2 radicals under the low-NO conditions of this study.…”
Section: Discussionmentioning
confidence: 99%
“…4). Inclusion of autoxidation reactions for peroxy radicals that do not lead to limonaldehyde production may also improve the model agreement with the measurements (27,52). Another possible explanation for the difference between the measurements and the model is the unknown fragmentation patterns of many oxygenated products in the PTR-ToF-MS drift tube and sampling loss in the perfluoroalkoxy (PFA) tubing, the latter of which was not quantified.…”
Section: Model Predictions Of Gas-phase Oxidation Products From Limon...mentioning
confidence: 99%